Margorejo Underpass Route Choice Study: Reviewed from Traffic Analysis - Wardani, Esti Kusuma (Journal of Transportation Study Forum, 2024)
The signalized intersection at Ahmad Yani street and Margorejo street becomes an intersection with quite long delays at peak hours. street Ahmad Yani is an arterial road that connects Surabaya to Sidoarjo. The presence of high frequency train tracks and a u-turn on the frontage road in front of Giant Maspion Square has resulted in reduced green time on the east side traffic light heading north. One effort to reduce this congestion is to build an underpass. Before an underpass is built, it is necessary to select an underpass route referring to the 1997 Indonesian Road Capacity Manual (MKJI). The results obtained in this final assignment are the determination of the Margorejo-Ahmad Yani route which is recommended for an underpass to be built because the large delay that occurs is 687 sec/smp on Jalan Ahmad Yani Sidoarjo-Surabaya; 1938 det/smp on Jalan Ahmad Yani Surabaya- Sidoarjo; 149 sec/smp on Jalan Margorejo; and 120 on the frontage road. The DS that occurred was 1.33 on Jalan Ahmad Yani Sidoarjo-Surabaya; 1.66 on Jalan Ahmad Yani Surabaya-Sidoarjo; 0.9 on Jalan Margorejo; and 0.22 on road frontage. The queue length was 648 secondary schools on Jalan Ahmad Yani Sidoarjo-Surabaya; 2422 junior high schools on Jalan Ahmad Yani Surabaya-Sidoarjo; 68 junior high school on Jalan Margorejo; and 18 junior high schools on the frontage road. With the construction of the Margorejo underpass, the DS on all sections will be 1,074 on Jalan Ahmad Yani Sidoarjo-Surabaya; 1,385 on Jalan Ahmad Yani Surabaya-Sidoarjo; 0.5 on Jalan Margorejo; and 0.07 on road frontage. Delays and long queues no longer exist because there are no longer traffic lights.